EIB Working Paper 2022/02 - How to foster climate innovation in the European Union Insights from the EIB Online Survey on Climate Innovation - European Investment Bank (European Investment Bank, 2022)
Relying on the EIB Online Survey on Climate Innovations, we investigate the different climate innovations European firms are currently using, their motivations and challenges, and their views on current regulatory frameworks. The analysis confirms that there's a strong link between climate innovation and firm performance, but also that firms suffer from the low availability of finance. To create more successful firms in the climate sector, European policymakers should strengthen policies that reduce regulatory uncertainty and work actively to improve access to finance conditions, in particular for start-ups.